The Effectiveness of Lending and Organizational Management on Increasing Income of Small and Medium Enterprises of UMKM in Medan City - Budi Dharma; Sonia Purba; Finik Kharianti (Penerbit Jurnal Indonesia, 2022)
MSMEs are one of the pillars of the economy in Medan City which is managed and run by the community. The existence of MSMEs is very helpful in meeting the needs of the community. The government also supports MSME development programs and the optimization of MSME so that they are more relevant to the needs and capabilities of the community. Control of MSME financial circulation must also be taken into account and considered because it affects the income of these MSMEs. The urgency of MSMEs is the main foundation of the purpose of this research in the form of knowing the effectiveness of lending and organizational management in increasing MSME income in Medan City. The research method used in this study is descriptive qualitative with data collection techniques in the form of interviews with respondents regarding MSME regulations that are oriented towards online loans and organizational management. The research results obtained indicate that there is a positive effectiveness of lending and organizational management which is directly provided by financial institutions for MSME owners in Medan City. The form of this effectiveness can be seen from the three variables, namely input variables, process variables and output variables. Organizational management carried out within the MSME environment is also considered effective because it has received a lot of information from other MSME actors and exchange ideas in increasing MSME income which is directly oriented towards organizational management.